2017
DOI: 10.1016/j.lfs.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic quercetin administration on methylphenidate-induced hyperlocomotion and oxidative stress

Abstract: These results suggest that chronic quercetin treatment has antimanic-like and antioxidant effects, thus encouraging further studies of quercetin as a putative new antimanic drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
2
16
0
1
Order By: Relevance
“…Other experimental studies have also established that the observed anti-oxidative properties of crocin in neurodegenerative disorders and diseases are mediated by an increase in activity of GR and GPx (Bors et al, 1984;Ochiai et al, 2004a). Moreover, a similar previous study demonstrated that prolonged quercetin treatment blocked the MPH-induced increase in oxidative stress (Kanazawa et al, 2017). Also, our results confirm prior studies showing a decrease in SOD action following MPH abuse (Lagace et al, 2006;Martins et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Other experimental studies have also established that the observed anti-oxidative properties of crocin in neurodegenerative disorders and diseases are mediated by an increase in activity of GR and GPx (Bors et al, 1984;Ochiai et al, 2004a). Moreover, a similar previous study demonstrated that prolonged quercetin treatment blocked the MPH-induced increase in oxidative stress (Kanazawa et al, 2017). Also, our results confirm prior studies showing a decrease in SOD action following MPH abuse (Lagace et al, 2006;Martins et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…It has been previously proposed that crocin can modulate cortical excitability, motor activity, and reaction speed in depressed individuals (Jam et al, 2017). A related study demonstrated that chronic administration of quercetin blocked MPH-stimulated hyper-locomotion in mice, which may reflect an antimanic-like effect (Kanazawa et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…AMPH-induced hyperlocomotion has been shown to be reversed [7] and prevented [49] by intraperitoneal administration of lithium or tamoxifen (TMX), a selective estrogen receptor modulator with PKC inhibitory activity [8,50]. Similarly, intraperitoneal administration of quercetin, a nonspecific PKC inhibitor, also prevented methylphenidate-induced hyperlocomotion [51]. Not only in the presence of pharmacological intervention, daily intraperitoneal administration of lithium or TMX alone for 7 days significantly decreases phosphorylated PKC (pPKC) in the hippocampus, PFC, amygdala, and striatum [7].…”
Section: Pkc Translocation and Activitymentioning
confidence: 99%
“…Kanazawa et al [53] showed that the quercetin administration was able to reverse the increase in lipid peroxidation in PFC, hippocampus, and striatum in a mouse model of mania induced by PSD. Quercetin also blocked methylphenidate-induced hyperlocomotion and oxidative stress in PFC, hippocampus, and striatum of mice [51]. It appears that oxidative stress is downstream to PKC signaling as TMX, a selective PKC inhibitor, also prevented and reversed oxidative stress in AMPH-treated rats [50].…”
Section: Downstream Targets Of Pkcmentioning
confidence: 99%